Pendampingan Kelompok Penangkar Benih Kedelai Binaan UD. Humfik Tani Untuk Meningkatkan Ketersediaan Benih Kedelai Bersertifikat - Kisman; Uyek Malik Yakop; A. Farid Hemon; B. Erna Listiana; Suprayanti Martia Dewi (Jurnal SIAR ILMUWAN TANI, 2020)
UD. Humfik Tani is one of the seed producers of "Rice and Soybean" which has many assisted seed breeders in Central Lombok. However, until now seed breeders have not been able to provide and procure soybean seeds as needed. The purpose of this community service activity was to provide theoretical and technical assistance to the soybean seed breeder group guided by UD. Humfik Tani in producing certified soybean seeds to increase the availability of certified soybean seeds. The method used in this service activity was the Adult Education (POD) or Androgogy method by emphasizing the active participation of participants, group work and field demonstrations. This mentoring activity was carried out in the form of counseling and field education (demonstration plots) which are conducted in Ubung village, Jonggat district. This activity was attended by 14 participants (UD. Humfik Tani, fostered breeders, UPT BPP, PPL, Tani Tunggal Angen). The results shows that 1) This service activity was going well and the participants were very earnest and enthusiastic about all activities ranging from counseling to visits to the demonstration plot location and were very interested in Biosoy 2 large seed soybeans. 2) UD. Humfik Tani was very interested and will develop Biosoy 2 certified soybean seeds in his breeding land and the breeders at MK II August 2020 to provide seed needs on MH December 2020